A Novel Method for Determining Angular Speed and Acceleration Using Sin-Cos Encoders - Manuel Alcázar Vargas; Javier Pérez Fernández; Juan M. Velasco García; Juan A. Cabrera Carrillo; Juan J. Castillo Aguilar (Sensors, 2021)
The performance of vehicle safety systems depends very much on the accuracy of the signals coming from vehicle sensors. Among them, the wheel speed is of vital importance. This paper describes a new method to obtain the wheel speed by using Sin-Cos encoders. The methodology is based on the use of the Savitzky–Golay filters to optimally determine the coefficients of the polynomials that best fit the measured signals and their time derivatives. The whole process requires a low computational cost, which makes it suitable for real-time applications. This way it is possible to provide the safety system with an accurate measurement of both the angular speed and acceleration of the wheels. The proposed method has been compared to other conventional approaches. The results obtained in simulations and real tests show the superior performance of the proposed method, particularly for medium and low wheel angular speeds.